Sex Workers and the Cost of Safe Sex : The Compensating Differential for Condom Use in Calcutta - Rao, Vijayendra; Gupta, Indrani; Jana, Smarajit (World Bank, Washington, DC, 2015)
The practice of safe sex by commercial sex workers is considered central to preventing the transmission of AIDS in developing countries. The authors estimate the compensating differential for condom use among sex workers in Calcutta, based on results from a survey conducted in 1993. If, as suggested by anecdotal evidence, this loss in income is large, it would indicate the existence of strong disincentives for practicing safe sex. To identify the relationship between condom use and the average price per sex act, they follow an instrumental variable approach, exploiting an intervention program focused on providing information about the AIDS virus and about safe sex practices. The program, instituted in 1992, was not systematically administered. Using this method, they found that sex workers who always use condoms face a loss of 79 percent in the average earnings per sex act.